Translating Cultural Words in a Movie Subtitle: A Study on Translation Procedures - Faiz Akbar Leksananda; Beatrice Phoebe Gantari Manusu (Universitas Sarjanawiyata Tamansiswa, 2023)
A gap of structure and meaning is often discovered between the conversations taking place in a movie and the displayed subtitle translation on the screen. Hence, this paper attempts to uncover types of cultural words as well as the translation procedures employed in The Dictator movie subtitle. Data sources were obtained from the paid streaming site, Netflix and scrutinized using a comparative descriptive approach. As many as 156 cultural words were discovered with nine procedures employed to translate those based on Newmark theories. Transference and literal translation were the two most frequent procedures applied in the subtitle. As a safe shortcut, the translator managed to employ transference which simply moves the text without any changes and literal translation to translate source texts according to its semantic features. As a result, the translation will be perfect in terms of faithfulness and acceptability yet weak in terms of naturalness, degree of informality, and fun.